2021
DOI: 10.5863/1551-6776-26.4.318
|View full text |Cite
|
Sign up to set email alerts
|

The Trilogy of SARS-CoV-2 in Pediatrics (Part 2): Multisystem Inflammatory Syndrome in Children

Abstract: Multisystem Inflammatory Syndrome in Children (MIS-C) was first recognized as a novel illness in 2020 with manifestations similar to other hyperinflammatory syndromes, such as Kawasaki disease or macrophage activation syndrome. Severity varies from a self-limited febrile illness to shock requiring inotropes and mechanical ventilation. Gastrointestinal symptoms and persistent fevers are the most common clinical symptoms, with the addition of cardiac manifestations inclusive of ventricular dysfunction and corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…These cytokines may be studied as new therapeutic options as well. Tran et al 20 suggested that IL-1 may play an important role in the pathology of MIS-C and SARS-CoV-2. They reported that especially IL-1 β is higher in MIS-C.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines may be studied as new therapeutic options as well. Tran et al 20 suggested that IL-1 may play an important role in the pathology of MIS-C and SARS-CoV-2. They reported that especially IL-1 β is higher in MIS-C.…”
Section: Discussionmentioning
confidence: 99%
“…In general, LMWH is preferred to UFH in pediatric patients due to good bioavailability, long duration of action and more studies supporting its use in the pediatric patient population [ 33 ]. The phase II trial, which was conducted in pediatric COVID-19 and MIS-C patients in order to investigate safety and optimal dose of enoxaparin, showed that based on the absence of clinically relevant bleeding events and other adverse effects within the prespecified range of dose, this medication is safe [ 24 ].…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…As MIS-C frequently affects the heart, we may need to perform B-type natriuretic peptide, cardiac enzymes and Troponin I or T, electrocardiogram, and echocardiography. According to the organs affected, other laboratory tests may be needed[ 96 ]. MIS-C is primarily treated with supportive care, fluid resuscitation, and inotropic support as a cardiogenic shock is one of the most severe presentations.…”
Section: Covid-19-induced Autoimmune Diseasesmentioning
confidence: 99%